Decreasing rates of natural deaths in a remote Australian Aboriginal community, 1996-2010 - Zaimin Wang; Wendy E. Hoy (Elsevier, 2013)
Abstract Objective : To examine the trends of all‐cause natural mortality for people aged 15 years and over in a remote Australian Aboriginal community between 1996 and 2010. Methods : The annual population in the community by gender and age group was obtained from the Australian Bureau of Statistics (ABS). All known deaths and all records of start of renal replacement therapy (RRT) for renal failure were recorded between 1996 and 2010. Five‐year aggregated death rates were calculated and the changes in natural mortality over the interval were evaluated. Mortality was compared with those of the Northern Territory (NT) Indigenous and non‐Indigenous people as a whole from 1998 to 2006. Results : Rates of natural deaths were lower in the third interval 2006-2010 relative to the first interval 1996-2000, with higher, but more rapidly falling rates for females than males. Reductions were prominent for both sexes in the 65 and over age groups, but death rates in females of earlier middle age also trended lower. The trends applied whether or not the starting of RRT was considered as a natural death. There was a similar trend in rates of natural death in the aggregate Indigenous population of NT. Conclusions: The downward trends probably reflect improvements in risk factor status since the 1960s, all‐of‐life health interventions, as well as better chronic disease management in the last two decades. The higher death rates in females than males in this community remain unexplained, but the rapid rate of decline of female death rates predicts that this gap will soon be minimised.